Approximations of elastic lateral displacement profiles for walls with openings. (February 2018) - Tena-Colunga, Arturo; Rivera-Hernández, Germán
Abstract: The assessment of lateral displacements is important in displacement-based design. Therefore, in this study the approximations obtained with different simplified methods used to assess the elastic lateral displacements of walls with openings are compared to results obtained with the finite element method using reasonably fine meshes. Multistory walls were studied, considering symmetric and asymmetric distribution of openings with respect to a vertical axis. From the obtained results it can be observed that for a single strip of asymmetric perforated walls, best approximations are obtained for slender walls using a version of the equivalent frame method where end zones are considered completely rigid, the method proposed by Coull and Choudhury, as well as a method proposed by the authors, named as the equivalent non-prismatic wide column analogy. Highlights: Lateral displacement profiles of walls with opening are assessed using simplified and the FEM methods The relative impact of the eccentricity of the opening ( e ) in lateral displacements is assessed. Lateral displacements increases as e increases Good approximations are obtained for the equivalent frame method when e is small. Good approximations are obtained with the equivalent shear connection method for slender walls regardless of e .